ELIMINATING TYPICAL ERRORS IN STUDENT SPEECH: CAUSES, TYPES, AND PEDAGOGICAL STRATEGIES (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
Every student slips up when learning to speak a new language — it’s normal. But when these mistakes stick around, they get in the way of clear communication and can drag down academic progress. This thesis digs into the most common errors in student speech, looks at why they happen, and lays out practical ways to tackle them. The focus is on hands-on instruction, useful feedback, and real-life speaking practice.